Correlation between the upper airway volume and Ricketts’ facial biotypes: a cone-beam computed tomography study - Ana Rita Carvalho; Maria Cristina Figueiredo Pollmann; Eugénio Joaquim Pereira Martins (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Objectives: This study aimed to determine if there are differences in the upper airway space between the three facial biotypes described by Ricketts. It also investigated if there are anatomical differences between males and females at the upper airway level. Methods: Data was collected from a private orthodontic clinic. Orthodontic tracing was done using NemoFab Ortho software to obtain the dentoskeletal measurements: anterior facial height, posterior facial height, maxillary width, and palatal depth. The upper airway measurements were achieved using the same software by identifying landmarks for each upper airway compartment (nasopharynx and oropharynx). The Pearson correlation coefficient was used to determine the correlation between the variables α=0.05). Results: The sample included eighty patients with a mean age of 30.4 years, predominantly females (67.5%). Statistical differences were found between brachyfacial and dolichofacial patients regarding the oropharynx volume (p=0.009) and total volume (p=0.027). Regarding the comparison by sex, male patients had significantly higher mean values for upper airway volumes and all the dentoskeletal features analyzed, except for maxillary width. Conclusions: There are statistical differences in the upper airway space among different facial biotypes. Brachyfacial patients seem to have higher upper airway volumes than Dolichofacial patients. Moreover, males showed higher upper airway volumes than females.